The crucial effect of early-stage gelation on the mechanical properties of cement hydrates - Katerina Ioannidou (Nature Portfolio, 2016)
The origins of the unique properties of cement are poorly understood. Using simulations the authors show that the early formation of a soft nano-particle gel, followed by slow densification, plays a crucial role in giving cement its unique mechanical properties.